Analisis Rekontruksi Organisasi dan Politik Pembangunan di Indonesia - Nabil Alwan; Eli Apud Saepudin; Mumun Komala Sari; Nanda Putra Pajar; Ria Purwasih (UNIVERSITAS SERAMBI MEKKAH, 2024)
Development in Indonesia has undergone various transformations and reconstructions since independence. This reconstruction involved changes in organizational structures and the underlying political system. Impact of Reconstruction on Development: Progress: Poverty alleviation and improved public welfare, Rapid economic growth especially in the New Order era, Development of democracy and public participation. Challenges: Economic inequality and social disparities remain high, Quality of education and health still needs to be improved, Environmental degradation and climate change.